O desenvolvimento sustentável na ordem constitucional e sua promoção através do planejamento urbano - Queiroz, Lizziane Souza (2009)
The man, being subject and object of their changes, has passed by many process to find a better life way. Since your existence, he finds to live in groups for make easy your life and make concrete yours desires. All by history, when the individual´s rights was establishment, collectives and lonely way, contribute for evaluate the relationship between individuals and they own, and them and state, which has a duty to those, positive or negative, depending on the case. The circle of fundamentals rights has been sustainable development and the concept of growth economy associated to the environment protection. This association reflect a apparent conflict between values very distinct, but the constitutional interpretation can be reunite both of them and make it live in harmony; values of environmental order and economical order can be exist together, as long as the state contribute to this. On the city, where the most of relationships happening, the urban plan appear how a effective way of sustainable development, finding the harmony between the growth economy and environment protection. To effective the socials functions of the city (inhabit, circulate, work and entertainment) and the citizen´s life quality, the city is the scenery that show how the urban plan, across established previously legal instruments, like the governmental public politics, to effective the right to development, right of third generation. The director plan how effective tool for local needs - obligation defined by Citizen Statute that contribute for the program linked defined by the urban plan. The state´s intervention on the private sector of citizen, and the restriction on their rights are be justified by the collective´s rights and their quality of life. So, in front the urban scenery has been the plan to make social functions of city, the healthy way of life, which is the sustainable development